A reforma curricular na área de Geografia a partir dos cadernos impressos dos alunos da Secretaria de Educação Estadual de São Paulo - Almeida, Natalia de (2017)
The present study is related to the curricular reform of the São Paulo state school network, which is currently underway, aiming to understand the connection between this new configuration of education proposed by the State of São Paulo Department of Education and its relation with the social and political conformation in force in the area of Education. This conceptual elaboration, present in the São Paulo Faz Escola Program by the São Paulo State Secretariat, began in 2011, and took the form of teacher training, production of teaching materials and various manuals. In an attempt to understand how the curriculum is proposed in the schools of São Paulo, the area of Geography was selected for the examination of the notebooks made available to the ninth grade students, considered as a common basis obligatory to the whole network among the other areas that make up the elementary school curriculum II. Therefore, the analysis of the didactic material present in the school organization and proposed by the curricular reform in question was carried out, especially the notebooks of the São Paulo Faz Escola Program intended for teachers and students in the classroom in Geography due to being the sphere of Performance of the researcher. For this analysis we used documentary data on educational policy and Weber's theoretical concepts for understanding the hierarchy of education, Gimeno on curriculum and tasks, Bloom and his colleagues to analyze the tasks stipulated in the eight learning situations and Chartier based on Analysis and description of the material. Each learning situation was analyzed as to what is asked the students to fulfill as tasks and classified by the cognitive categories to identify the level of teaching proposed to these students. The analysis data were organized in frames each Learning situation and a final table that shows the frequency of each of these cognitive categories, consequently the expected level of learning when it is fulfilled, a focus that was not the object of this study in the reality of the classrooms. The results demonstrate the presence Learning situations organized in a way that Centered on tasks of lower cognitive level with more than half of the tasks aimed at the acquisition and standardized understanding of knowledge, necessary, but not sufficient for the formation of the pupil